Management of an emergency tooth extraction in diabetic patients on the dental chair - Giath Gazal (Saudi Dental Journal)
Background and objective: Approximately 75% of diabetic patients in Saudi Arabia had poor glycaemic control. A high proportion of these patients will attend dental surgery clinics for treatment. Therefore, dentists should be well-prepared to control any complications they might arise on the dental chair during the dental procedures. Management of the associated risk factors is important to limit disease complications and improve the health of patients with diabetes.The objectives of this review were to determine the maximum acceptable level of blood glucose for tooth removal in diabetics, show a systematic technique for the management of patients with diabetes on the dental chair. By using PRISMA guidelines, analysis of the published articles and reports across the world is considered one of the most appropriate available methods to obtain strong evidence about the acceptable levels of blood glucose where teeth extraction can be done safely. Results: A total of 1080 studies were retrieved using the search strategy. After screening 185 titles, abstracts and 85 full-text articles, 36 studies were included. The outcome of this systematic review revealed that fasting blood glucose level of 240 mg/dl is a critical point for any dental treatment because the warning signs of diabetes start coming out. Maximum acceptable levels of blood glucose for removal of teeth in diabetics are 180 mg/dl (before meal) and 234 mg/dl (2 h after a meal). High blood glucose levels reduce the secretion of nitric oxide (powerful vasodilator) in the body which leads to poor circulation and slow-healing socket. Uncontrolled diabetics are at high risk of infection because of the high ketone levels in the blood. Conclusion: Fasting blood glucose level of 180 mg/dl is a cut-off point for any selective dental extraction. However, Random blood glucose level of 234 mg/dl (13 mmol/l) is a cut-off point for an emergency tooth extraction. Tightly controlled diabetic patients (blood glucose level below 70 mg/dl) are susceptible to hypoglycemia. Keywords: Management, Tooth extraction, Diabetic patients, Blood glucose cut-off points